Development of ternary binder mixing formulation for asphalt pavement recycling - Savarnya A.; Saboo N.; Das A.; Makowska M.; Pellinen T. (My University, 2025)
Recycling agents (as softening agents or, rejuvenators) are being widely used in the asphalt recycling process. At the binder level, recycling therefore involves three constituents, namely, virgin binder, aged binder (arising out of reclaimed asphalt pavement materials) and the recycling agent–making it a ternary binder blend. Limited literature is available on the ‘mixing formula’ for ternary binder blend that can be used to predict the resultant physical property of the blend, when the proportion and physical property of each of these three binders are given. The objective of the present research is to explore a suitable ternary mixing formula (relevant to hot asphalt recycling process) based on empirical observations in the laboratory. In this work, four different types of recycling agents (two softening agents and two rejuvenators) are used, and the complex viscosity is taken as the physical property. Temperature and frequency are also included as variables as an effort to improve the robustness of the suggested equation. Subsequently, a generalised equation is developed for the prediction of complex viscosity at any given temperature and frequency and the same is validated for the ternary binder mix dealt in the present study. © 2021 Informa UK Limited, trading as Taylor & Francis Group.